Deep dynamic pools of phosphorus in the sediment of a temperate lagoon with recurring blooms of diazotrophic cyanobacteria - Todd R. Scicluna; Ryan J. Woodland; Yafei Zhu; Michael R. Grace; Perran L. M. Cook (Limnology and Oceanography, 2015)
The storage and release of phosphorus by sediments can act as an important control on the formation of noxious blooms of cyanobacteria in lakes and estuaries. Here we studied the uptake and release of phosphorus associated with iron oxides within sediments of a lagoon system affected by recurring summer blooms of the cyanobacterium Nodularia spumigena . Using an ascorbate extraction, we observed deep pools of iron oxide associated phosphorus (P) at concentrations of ∼5 μ mol g −1 dry sed to a depth of ∼20 cm. This pool rapidly decreased with the onset of water column anoxia, leading to an integrated release of ∼300 mmol of phosphorus m −2 of sediment over 3.5 months. Scaling this flux over the periodically anoxic area of the lake and over the period of an N. spumigena bloom (November–December 2011) gave a broad mass balance agreement with the increase in total phosphorus within the water column and exported from the lagoon. Over this period we estimated that P release from the sediment would have allowed ∼130–187 tonnes of nitrogen to be fixed which agrees with previous estimates of nitrogen fixation. Upon reoxygenation of the water column, a regeneration of the deep iron oxide associated phosphorus pool was observed. This deep dynamic pool of phosphorus was most likely mediated by the burrowing activity of the polychaete Capitella capitata which was observed at the study site. This study underscores the potential importance of sediments colonized by deeply irrigating fauna to become a significant source of phosphorus during water column anoxia.